SISTEM TRANSMISI DATA ELEKTROMAGNETIK DENGAN MODUL RF XBEE UNTUK MENGETAHUI PENGARUH FUNGSI SPASIAL DAN FUNGSI TEMPORAL TERHADAP PROSES TRANSMISI GELOMBANG ELEKTROMAGNETIK - Eka S, Aprilian; Prima N, Yayan; B, Hanif; Mashudi, M; M, Adiyatno (Universitas Negeri Surabaya, 2014)
Computational Laboratory work based research and development is an implementation of the study of physics topics of Electromagnetic Waves. In this physical event it will be studied in the treatment of Electromagnetic Waves transmit information. Delivery Information in this study using the XBee modules as media delivery and acceptance of this research will be tested how the XBee modules were subjected to the measurement of the spatial variation influences the efficiency of data transmission. Change the time variation performed three times for each variation of the distance change measurements. The third shows the time variation of the same relative results are collecting data at 5:00 to 7:00 showed the best distance is obtained at a distance of ? 75 m, while for a distance of 80 m to 85 m of data at the receiver experiencing annihilation one character at a distance of 90 m and the data can not be accepted at all by the recipient. The data at 14:00 to 16:00 showed similar results also with the data obtained in the 20:00 to 22:00, that all significant data with the data of data at 5:00 to 7:00. The conclusion that can be drawn is that there is no significant effect of changes in -time delivery of data.